2022
DOI: 10.3389/fendo.2022.939366
|View full text |Cite
|
Sign up to set email alerts
|

High Maternal Total Cholesterol Is Associated With No-Catch-up Growth in Full-Term SGA Infants: The Japan Environment and Children’s Study

Abstract: ObjectivesInfants born small for gestational age (SGA) with no catch-up growth (No-CU) are at high risk of intellectual and developmental disabilities. However, factors leading to No-CU among SGA infants are unclear. This study aimed to examine the association between maternal total cholesterol (TC) in mid-pregnancy and No-CU at 3 years among full-term SGA infants.Study DesignThe Japan Environment and Children’s Study (JECS) is a nationwide prospective birth cohort study. We extracted a total of 2,222 mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“… 29 Kaneko et al also found that high total cholesterol levels in the second trimester of pregnancy can lead to deviations in infant growth. 30 Our study did not have such information as mentioned above.…”
Section: Discussionmentioning
confidence: 95%
“… 29 Kaneko et al also found that high total cholesterol levels in the second trimester of pregnancy can lead to deviations in infant growth. 30 Our study did not have such information as mentioned above.…”
Section: Discussionmentioning
confidence: 95%